Pollution Status of Raman River, Metro City Based on the Macrozoobenthos Community - Rena Yolanda; Henni Wijayanti Maharani; Rara Diantari; Indra Gumay Yudha (AQUASAINS, 2021)
Raman River is located in Purwoasri Village, North Metro District, Metro City. People use this river for various purposes, namely irrigation for rice fields , fisheries, transportation, tourism, and other uses. The increasing use of rivers by the community might caused a negative impact to the waters quality and affect the organisms living there, such as macrozobenthos. The purpose of this study was to analyze the pollution status of the Raman River waters based on the macrozoobenthos community structure. Sampling was done from April to Mei 2020. The research location was determined using a survey method and the sampling was carried out by purposive sampling. The data obtained were analyzed using Abudance-Biomass Comparison (ABC) method. The analysis showed that Raman River is moderately contaminated.Keywords: macrozoobenthos, Raman River, pollution stastus